A 6-year review of brain tumors at a national referral hospital in Kampala, Uganda - James J. Yahaya; Advera I. Ngaiza (Egyptian Journal of Neurosurgery)
Abstract Introduction Brain tumors (BTs) are a group of heterogeneous tumors which are aggressive and have significant morbidity and mortality globally. Aim of the work This study aims to provide a 6-year review of the frequency of histological subtypes of BTs from a single tertiary hospital in Uganda. Methods This was a descriptive cross-sectional study which included retrospective data from hospital records. Data were extracted from the patients’ files who were managed due to BTs in the neurosurgery unit from January 2013 to December 2018. Patients with available files and histology reports altogether with information consisting of histopathological diagnosis and clinical information on duration of diseases, and treatment modality among many others were included in the analysis. Results A total of 88 histologically confirmed cases with BTs were recorded at the neuropathology unit for a period of 6 years. The mean age of the patients was 35.3 ± 19.2 years, and males were slightly more prevalent 51.1% (45/88) compared to females. Most of the patients 54.5% (48/88) were presenting clinically with headache. Of all the cases analyzed, the vast majority 71.6% (63/88) of the patients had benign tumors. Gliomas were the most common BTs which were found in 44.3% (39/88) followed by meningiomas which comprised 40.9% (36/88). Astrocytomas were the commonest type of gliomas which consisted of 38.5% (15/39) of all the gliomas. Conclusion This study reports on a cohort of patients with BTs among whom, most of them were presenting clinically with headache. From our findings, it can be observed that the highest referral for acute neurosurgical intervention is glioma, followed by meningioma.